Signature of circulating microRNAs in patients with acute heart failure. (8th September 2015) - Ovchinnikova, Ekaterina S.; Schmitter, Daniela; Vegter, Eline L.; ter Maaten, Jozine M.; Valente, Mattia A.E.; Liu, Licette C.Y.; van der Harst, Pim; Pinto, Yigal M.; de Boer, Rudolf A.; Meyer, Sven; Teerlink, John R.; O'Connor, Christopher M.; et al.
Abstract : Aims: Our aim was to identify circulating microRNAs (miRNAs) associated with acute heart failure (AHF). Methods and results: Plasma miRNA profiling included 137 patients with AHF from 3 different cohorts, 20 with chronic heart failure (CHF), 8 with acute exacerbation of COPD, and 41 healthy controls. Levels of circulating miRNAs were measured using quantitative reverse transcription–polymerase chain reaction (qRT–PCR). Plasma levels of miRNAs in patients with AHF were decreased compared with CHF patients or healthy subjects, whereas no significant changes were observed between acute COPD patients and controls. Fifteen miRNAs found in the discovery phase to differ most significantly between healthy controls and patients with AHF were further investigated in an extended cohort of 100 AHF patients at admission and a separate cohort of 18 AHF patients at different time points. Out of these 15 miRNAs, 12 could be confirmed in an additional AHF validation cohort and 7 passed the Bonferroni correction threshold (miR‐18a‐5p, miR‐26b‐5p, miR‐27a‐3p, miR‐30e‐5p, miR‐106a‐5p, miR‐199a‐3p, and miR‐652‐3p, all P < 0.00005). A further drop in miRNA levels within 48 h after AHF admission was associated with an increased risk of 180‐day mortality in a subset of the identified miRNAs. Conclusions: Declining levels of circulating miRNAs were associated with increasing acuity of heart failure. Early in‐hospital decreasing miRNA levels were predictive for mortality in a subset of miRNAs in patients with AHF. The discovered miRNA panel may serve as a launch‐pad for molecular pathway studies to identify new pharmacological targets and miRNA‐based therapies.